Void detection of cementitious grout composite using single-walled and multi-walled carbon nanotubes. (January 2019) - Lee, Heeyoung; Kang, Donghoon; Kim, Jongwon; Choi, Kyungwho; Chung, Wonseok
Abstract: Cement-based materials containing carbon nanotubes (CNT) has enhanced electrical and thermal characteristics. This study aimed to detect voids in prestressed concrete (PC) grout using CNT. CNT cement grout specimens were fabricated and tested inside ducts. Test parameters were type of CNTs, concentration of CNTs, and void ratio of grout. Thermal imaging analysis and electrical resistance analysis were performed to detect and identify the void configuration. The field emission scanning electron microscopy (FE-SEM) images were taken to obtain detailed information of microstructure of tested specimen. It was concluded that MWCNT grout was appropriate to detect the void in duct using thermal image analysis. SWCNT grout was more suitable to identify void in duct through electrical resistance analysis.